The Importance of a Father Figure in the Process of Career Choice: A Comparative Study Among University Students - Lopes, Sandra Almeida (2011)
The objective of the research was to verify if the young who did not count on the father’s presence during his development choose some substitute figure and if his absence caused implications in his professional choice. Was applied the Drawing-Story with subject and a semi-directed interview, with twelve university students, both sexes, between 18 and 25 years. Half of the sample didn’t live with the father/stepfather in childhood and/or adolescence (group 1), the half was by his presence (group 2). In both groups, were determining factors in deciding his own interest/desire, returns, and field work. Half of the group 1 choose a substitute figure, the other half, it did not occur, there was the influence of the maternal figure in career choice. There are indications that in face of father and a surrogate figure absences, the mother assumes a significant place in this scenario.